Zinc and Linoleic Acid Protect Against Behavioural Deficits In Rat Model Of Parkinsonism Induced With Rotenone (African Journal of Biomedical Research, 2020)
Little is known about the behavioural effect of either Zinc or Linoleic acid or their combination in the delay of onset of Parkinson’s disease. This study was designed to investigate the effects of Zinc and Linoleic acid in the protection of behavioural deficits in rotenone-induced Parkinsonism in rats. Thirty six young adult female rats weighing 100-150 grams divided into six groups were used. Rats were induced with Parkinsonism by subcutaneous administration of rotenone (Sigma-Aldrich, St. Louis, SA) (2.5mg/kg) once a day for seven consecutive days. Rats  received (Dimethyl sulfoxide) DMSO/Olive oil or rotenone dissolved in DMSO/Olive oil. Groups III and IV received Zinc (30mg/kg) or Linoleic acid (150µl/kg) while group V received a combination of both, two weeks prior to rotenone injection. Groups II and VI served as negative (rotenone group) and positive (Levodopa groups) controls respectively. Measurement and analysis of behavioural function in rats employed a battery of tests including Elevated Plus Maze (EPM), Open Field Test (OFT), Novel Scent and Block Tests. Rats receiving rotenone displayed bradykinesia and motor impairment in the OFT, anxiety, decrease in olfactory acuity and discrimination in EPM, and Novel Scent Test respectively. The significant increase in postural instability, impaired motor activity/coordination, increased anxiety and the decrease in rearing behaviour caused by rotenone induction was attenuated significantly by treatment with Zinc and Linoleic acid, but not their combination. These results suggest that Zinc possess significant behavioural activity while Linoleic acid improves certain aspects of sensory and motor function than their combination